Carbohydrate-protein drink improves time to exhaustion after recovery from endurance exercise - Niles, E. S.; Lachowetz, T.; Garfi, J.; Sullivan, W.; Smith, J. C.; Leyh, B. P.; Headley, S. A. (European Journal of Applied Physiology, 2001)
Ten endurance trained males were studied to investigate the ergogenic effects of isocaloric carbohydrate (CHO, 152.7 g) and carbohydrate-protein (CHO-PRO, 112 g CHO with 40.7 g PRO) drinks ingested after a glycogen lowering diet and exercise bout. Treatments were administered in a double-blind and counterbalanced fashion. After a glycogen lowering diet and run, two dosages of a drink were administered with a 60 min interval between dosages. The CHO-PRO trial resulted in higher serum insulin levels (60.84 vs 30.1 mU/ml) 90 min into recovery than the CHO only trail (p<0.05). Furthermore, the time to run to exhaustion was longer during the CHO-PRO trial (540.7±91.56 sec) than the CHO only trial (446.1±97.09 sec, p<0.05). In conclusion, a CHO-PRO drink following glycogen depleting exercise may facilitate a greater rate of muscle glycogen resynthesis than a CHO only beverage, hasten the recovery process, and improve exercise endurance during a second bout of exercise performed on the same day.